2012
DOI: 10.1002/uog.12315
|View full text |Cite
|
Sign up to set email alerts
|

Counseling in fetal medicine: agenesis of the corpus callosum

Abstract: In this Review, we aim to provide up-to-date and evidence-based answers to common questions regarding the diagnosis and prognosis of prenatally detected agenesis of the corpus callosum (ACC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
171
3
12

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(192 citation statements)
references
References 56 publications
6
171
3
12
Order By: Relevance
“…It has been reported that the US diagnosis of CCA is associated with a false-positive rate of 0-20%, thus underlying the contribution of magnetic resonance imaging (MRI) [4]. The anterior part of the CC is usually better delineated by US (using an anterior transfontanellar approach) while the posterior part is better depicted by MRI (fig.…”
Section: Corpus Callosum Dysgenesismentioning
confidence: 99%
“…It has been reported that the US diagnosis of CCA is associated with a false-positive rate of 0-20%, thus underlying the contribution of magnetic resonance imaging (MRI) [4]. The anterior part of the CC is usually better delineated by US (using an anterior transfontanellar approach) while the posterior part is better depicted by MRI (fig.…”
Section: Corpus Callosum Dysgenesismentioning
confidence: 99%
“…In this classification, "isolated type" is without any other abnormalities, while "complex type" is concomitant with cerebral or extracerebral abnormalities such as holoprosencephaly, cyst formation, metabolic diseases. [14,15] Taking into consideration the mentioned classifications, this case is a partial agenesis according to Kidron classification, and presence of colpocephaly is appropriate with Type 1 of Brescian classification, but without magnetic resonance imaging it was not possible to evaluate Probst bundles. [7,13] Lastly, it may be considered as complex type of corpus callosum agenesis, due to accompanying poor academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Only 50% of the agenesis of corpus callosum and posterior fossa abnormalities are detected at the morphologic scan. However, this hypothesis should be verified in large population studies [24][25][26].…”
Section: Limitations Of the First Trimester Scanmentioning
confidence: 95%